The Effect of Ball Handling Training on Improving Basic Dribbling Technique of Basketball Players at Samudra Muda Basketball Club East Tanjung Jabung Regency (COMPETITOR: Jurnal Pendidikan Kepelatihan Olahraga, 2025)
This study aims to determine the effect of ball handling training on improving the basic dribbling technique of basketball students at Samudra Muda Basketball Club, East Tanjung Jabung Regency. This study used a quantitative descriptive approach with a pre-experimental design, specifically a group pretest-posttest design. The population consisted of 15 male students who were members of the Samudra Muda Basketball Club. The sample comprised 10 male students selected using a purposive sampling technique based on predetermined criteria. The instrument used was a zigzag dribbling test for basketball. Data collection was conducted through 16 training sessions over 4 weeks, with a frequency of 3 times per week. Data analysis used a paired sample t-test with SPSS 26. The results showed a significant difference between pretest and posttest scores. The pretest mean score was 27.30, while the posttest mean score was 40.10, showing an improvement of 12.80 points. The t-test results showed t-count (-12.551) > t-table (2.262) with a significance value of p = 0.000 < 0.05.